Development and characterization of conductive ring spun hybrid yarns. Issue 1 (2nd January 2019) - Shahzad, Amir; Ali, Zulfiqar; Ali, Usman; Khaliq, Zubair; Zubair, Muhammad; Kim, Ick Soo; Hussain, Tanveer; Khan, Muhammad Qamar; Rasheed, Abher; Qadir, Muhammad Bilal
Abstract: Development of conductive yarns for smart textile applications is the most demanding area of research these days. This study was aimed to investigate the effect of yarn constructional parameters, and relative humidity on electromechanical properties of conductive ring spun hybrid yarns. Stainless steel (SS) fibre was blended with polyester and viscose fibre separately on 12% and 24% weight basis to produce hybrid conductive yarns at three different levels of twist factor. The electromechanical properties of yarns were evaluated in response to change in blend type, blend ratio, twist factor, and relative humidity. The content of SS fibre is found to be more effective followed by the twist factor and blend type to govern the linear electrical resistance (LER) of conductive yarns. In addition, on increasing relative humidity, the LER of viscose stainless steel (VS) hybrid yarns are found to drop significantly than that of polyester stainless steel (PS) hybrid yarns.